Map of the Development of STEM Learning Research in Elementary Schools in Indonesia - Tita Hasanah (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to map the development of STEM learning research in elementary schools in Indonesia based on scientific publications indexed in the Scopus database. Data were searched using search strings that combined the terms STEM, elementary school, and the Indonesian context. Data analysis was conducted using descriptive qualitative methods, including annual publication trends, document types, and subject field distribution. A total of 123 documents were obtained from 2005 to 2025. The results showed that publications on STEM learning increased significantly after 2019, declined during the COVID-19 pandemic, and increased again in recent years. Journal articles dominated the document types, while the most studied fields included social sciences, physics and astronomy, mathematics, and computer science. These results indicate that STEM studies in elementary schools continue to develop and involve various disciplines. The findings of this study provide an overview of the direction of STEM research development in Indonesia and identify potential for further studies that can use a more diverse database, so that future research mapping can be carried out more comprehensively. This study is expected to serve as a basis for curriculum development, education policy, and further research on the implementation of STEM learning in Indonesia